Radar-derived Friction Velocity along RV MARIA S. MERIAN cruise track MSM89 - Michael Streßer; Ruben Carrasco; Jochen Horstmann; Johannes Karstensen (PANGAEA, 2023)
The dataset contains processed and quality controlled underway measurements of the magnitude of the (air-side) friction velocity between January 18, 2020 and February 19, 2020. The observations are derived from radar data acquired with a Hereon X-band marine radar. The radar was deployed on the research vessel Maria S. Merian during the research cruise MSM89 for the EUREC4A-OA project.